2006
DOI: 10.1111/j.1365-2141.2006.06110.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in patients with sickle cell disease: a longitudinal study

Abstract: SummaryAlthough pulmonary hypertension (PHT) is a common complication in patients with sickle cell disease (SCD), the rate of development of PHT and the factors that affect disease progression are unknown. We observed 93 patients over a median follow-up period of 2AE6 years (range 0AE2-5AE1 years). Data were censored at the time of death or loss to follow-up. Pulmonary hypertension was associated with an increased risk of death (relative risk, 9AE24; 95% confidence interval: 1AE2-73AE3; P ¼ 0AE01). There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
267
5
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(295 citation statements)
references
References 37 publications
10
267
5
13
Order By: Relevance
“…In particular, some of the variability in Hb F expression is attributable to functional alleles in the fetal hemoglobin genes inherited on specific b S -globin haplotypes [48,[51][52][53]. Fetal hemoglobin expression may be relevant to pulmonary hypertension, as this and other studies have observed significantly lower levels of Hb F in SCD pulmonary hypertension cases (Table IV) [9,10]. However, the haplotype analysis would predict that the strongest loci underlying this effect would be present outside the b-globin locus.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In particular, some of the variability in Hb F expression is attributable to functional alleles in the fetal hemoglobin genes inherited on specific b S -globin haplotypes [48,[51][52][53]. Fetal hemoglobin expression may be relevant to pulmonary hypertension, as this and other studies have observed significantly lower levels of Hb F in SCD pulmonary hypertension cases (Table IV) [9,10]. However, the haplotype analysis would predict that the strongest loci underlying this effect would be present outside the b-globin locus.…”
Section: Discussionmentioning
confidence: 79%
“…Perhaps intravascular hemolysis represents a lower fraction of total hemolysis in Hb SC than is the case in homozygous SCD. However, anemia, renal insufficiency, elevated alkaline phosphatase, and excess iron remain consistent distinguishing characteristics across all SCD pulmonary hypertension patients (Table V) [5,10]. Prior studies have documented phenotypic associations between pulmonary hypertension, hemolysis, and priapism in patients who may have less frequent vasoocclusive manifestations [2,5,36].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Similarly, an increase in pulmonary artery systolic pressure, also as assessed by Doppler echocardiography, is associated with an increased risk of death in individuals older than 45 years without SCD. 7 In SCD, the risk of developing an elevated TRV increases with age, hemolysis (defined by indirect markers of hemolysis), renal insufficiency (defined as an elevated creatinine level), iron overload (defined as an elevated ferritin level), and systemic hypertension (defined as an elevated systolic systemic blood pressure).…”
Section: Introductionmentioning
confidence: 99%
“…7 In SCD, the risk of developing an elevated TRV increases with age, hemolysis (defined by indirect markers of hemolysis), renal insufficiency (defined as an elevated creatinine level), iron overload (defined as an elevated ferritin level), and systemic hypertension (defined as an elevated systolic systemic blood pressure). 2,5,6 Chronic intravascular hemolysis has been shown to cause endothelial dysfunction (defined as a resistance to nitric oxide-mediated vasodilation or impaired responses to L-NMMA or acetylcholine 8,9 ) secondary to the nitric oxidescavenging effects of plasma hemoglobin and catabolism of L-arginine by erythrocyte arginase 1. 10 These mechanisms suggest that therapeutic interventions enhancing the effects of nitric oxide could be beneficial.…”
Section: Introductionmentioning
confidence: 99%